Tunable electronic and optical properties of the WS2/IGZO heterostructure via an external electric field and strain: a theoretical study. Issue 27 (20th June 2019) - Tang, Hongyu; Tan, Chunjian; Yang, Huiru; Zheng, Kai; Li, Yutao; Ye, Huaiyu; Chen, Xianping; Fan, Xuejun; Ren, Tianling; Zhang, Guoqi
Abstract : The external mechanical strain can efficiently modulate the photoresponse of the WS2 /IGZO heterostructure to the UV light and the visible light. Abstract : In this study, the structural, electronic and optical properties of a tungsten disulfide (WS2 ) hybrid with indium–gallium–zinc-oxide (IGZO) heterostructures were investigated based on density functional theory (DFT) calculations. According to the results of binding energy, charge density difference and electron localization function of heterostructures, we found that the WS2 and IGZO monolayers were bound to each other via non-covalent interactions with large binding energy. The calculated results illustrate that the AAii stacking pattern has an indirect band gap of 1.643 eV, while AAi and AB stacking patterns have maximum direct-gaps of 1.102 eV and 1.234 eV, respectively. Under an external E-field and mechanical strain, the response of the energy gap of the WS2 /IGZO heterostructure monotonically decreased over a wide range, even with a semiconductor–metal transition. In addition, we investigated the optical properties of the heterostructure and found that it exhibits a much broad spectral responsivity (from visible light to deep UV light) and a more pronounced optical absorption than WS2 and IGZO monolayers. Moreover, the tensile strain could weaken the photoresponse of the heterostructure to the UV light and enhance the response for the visible light; under compressive strain, the heterostructure showed a strong absorption peak in the UV light. Meanwhile, a red-shift was observed under an external strain. All these unique and tunable properties indicate that the WS2 /IGZO heterostructure is a good candidate for nanoelectronic and photoelectronic devices, such as field-effect transistors, flexible sensors, photodetectors and photonic devices.